Proteomics Revealed Distinct Responses to Salinity between the Halophytes Suaeda maritima (L.) Dumort and Salicornia brachiata (Roxb) - Benjamin, Jenifer Joseph (Plants (Basel), 2020)
Plant resistance to salinity stress is one of the main challenges of agriculture. The comprehension of the molecular and cellular mechanisms involved in plant tolerance to salinity can help to contrast crop losses due to high salt conditions in soil. In this study, Salicornia brachiata and Suaeda maritima, two plants with capacity to adapt to high salinity levels, were investigated at proteome level to highlight the key processes involved in their tolerance to NaCl. With this purpose, plants were treated with 200 mM NaCl as optimal concentration and 500 mM NaCl as a moderate stressing concentration for 14 days. Indeed, 200 mM NaCl did not result in an evident stress condition for both species, although photosynthesis was affected (with a general up accumulation of photosynthesis-related proteins in S. brachiata under salinity). Our findings indicate a coordinated response to salinity in both the halophytes considered, under NaCl conditions. In addition to photosynthesis, heat shock proteins and peroxidase, expansins, signaling processes, and modulation of transcription/translation were affected by salinity. Interestingly, our results suggested distinct mechanisms of tolerance to salinity between the two species considered, with S. brachiata likely having a more efficient mechanism of response to NaCl.